DANCING WITH THE COVID-19 PANDEMIC: How Indonesian Ketofastosis Community Express their Healthy Lifestyle on Facebook - Suryaman, Inge Salsabila; Wijaya, Bambang Sukma (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2020)
This article exposes how the Indonesian Ketofastosis (KF) community through the Facebook group expresses a healthy lifestyle, cultural practices online, views, and social movements related to the Covid-9 pandemic. Using the netnographic method, we found three main points that stand out in the community: 1) efforts to legitimize lifestyle, 2) sharing and caring practices, 3) social responsibility. Health issues related to Covid-19, such as 'Covid-19 victims mostly have high blood sugar history' or 'Ketoers are more immune than non-Ketoers,' becoming a "logical anchor" for some community members to strengthen their reasons for choosing the KF lifestyle. Several members also shared their experiences of living a healthy lifestyle in the face of the pandemic. Furthermore, administrators and several other members were motivated to carry out social activities by assisting frontline health workers who treat Covid-19 patients. It confirms that the Indonesian KF community has a sense of community as well as social responsibility. This study helps understand the micro-social phenomena associated with a pandemic outbreak. To cite this article (7th APA style):Suryaman, I. S. & Wijaya, B. S. (2020). Dancing with the Covid-19 Pandemic: How Indonesian Ketofastosis Community Express their Healthy Lifestyle on Facebook. Journal Communication Spectrum: Capturing New Perspectives in Communication, 10(2), xx-xx. http://dx.doi.org/10.36782/jcs.v10i2.2099